2016
DOI: 10.1111/papr.12425
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine as a Sedative in the Awake Implantation of a Neuromodulative System

Abstract: In this study group, dexmedetomidine combined with remifentanil provided a high level of patient satisfaction and comfort, as well as operator comfort, without any clinically relevant adverse events. All patients were highly cooperative and instructable; incident pain needs to be closely monitored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
1
5
1
Order By: Relevance
“…This report seems to be in contradiction with our own proof‐of‐concept study in which we describe the successful application of dexmedetomidine in the awake implantation of a neuromodulative system …”
Section: In Responsecontrasting
confidence: 97%
“…This report seems to be in contradiction with our own proof‐of‐concept study in which we describe the successful application of dexmedetomidine in the awake implantation of a neuromodulative system …”
Section: In Responsecontrasting
confidence: 97%
“…On the other hand, respiratory depression is an important side effect of other sedatives such as propofol, benzodiazepines, and opioids. The main side effects of dexmedetomidine are hypotension and both effects disappear quickly after stopping the infusion (1,(8)(9)(10).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the need for perioperative evaluation of the stimulation pattern, we investigated the efficacy of dexmedetomidine as sedative. It has been shown by ter Bruggen et al that percutaneous lead placement with dexmedetomidine as a sedative is safe and comfortable for patient and surgeon (1). There is also a case report by Harned et al where dexmedetomindine was used for surgical lead placement via laminectomy (2).…”
Section: Introductionmentioning
confidence: 99%
“…Dexmedetomidine is an alpha-2 agonist with sedative, analgesic, and anxiolytic properties, known for its ability to produce arousable sedation in a moderately sedated patient, with spontaneous ventilation. 8 Previous studies have reported promising results regarding the use of dexmedetomidine in awake procedures, such as during an awake craniotomy and during the surgical implantation of paddle lead electrodes for neurostimulation through alaminectomy. 9,10 In the DexMedPro trial, we compared dexmedetomidine with propofol during the implantation of a neurostimulator -as a sedative agent -in terms of patient satisfaction and safety.…”
Section: Introductionmentioning
confidence: 99%